Sistem Inventaris Web untuk Efiensi Stok Barang pada Toko Terang Abadi - Tegar Danuarta Kusuma; Anwar Nur Wahid; Taufiq Darmawan; Edy Susena (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
Manual inventory management at Toko Terang Abadi presents various challenges, including delays in reporting and high recording errors. This study aims to improve accuracy and efficiency in stock management by creating a web-based inventory information system using the Waterfall method. Data collection was conducted through interviews, direct observation of store activities, and literature review. The system was designed and implemented using PHP and MySQL, and tested using black-box testing methods to ensure all functions work according to user needs. Implementation results show that recording efficiency increased by 50% and input errors decreased by 90%. These findings support previous research highlighting the importance of digitalizing inventory systems in the SME and retail sectors to improve effectiveness and accuracy in managerial decision-making.